2010
DOI: 10.1002/path.2716
|View full text |Cite
|
Sign up to set email alerts
|

Implication of adenylyl cyclase 8 in pathological smooth muscle cell migration occurring in rat and human vascular remodelling

Abstract: Recently, we discovered on primary cell cultures that adenylyl cyclase type 8 (AC8) was involved in the transition of rat vascular smooth muscle cells (VSMCs) to an inflammatory phenotype. Here we demonstrate, in human vessels displaying early or advanced atherosclerotic lesions, that: (a) only intimal VSMCs strongly express AC8; and (b) very few AC8-positive VSMCs were detected in the medial layer, either in atherosclerotic or healthy arteries. Furthermore, over-expressing AC8 in primary rat VSMC cultures tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
4
16
0
3
Order By: Relevance
“…A similar tendency was observed for SM22 expression although its expression still seemed low at this time. This was consistent with the completion of neointimal formation usually occurring between 14 and 21 days postinjury when neointimal as well as medial VSMCs regain a differentiated state (15). In accordance with the in vitro findings mentioned above, AC8 expression opposed that of Notch3.…”
Section: Notch 3 and Ac8 Expression Are Reciprocally Related In Vivo-supporting
confidence: 78%
See 3 more Smart Citations
“…A similar tendency was observed for SM22 expression although its expression still seemed low at this time. This was consistent with the completion of neointimal formation usually occurring between 14 and 21 days postinjury when neointimal as well as medial VSMCs regain a differentiated state (15). In accordance with the in vitro findings mentioned above, AC8 expression opposed that of Notch3.…”
Section: Notch 3 and Ac8 Expression Are Reciprocally Related In Vivo-supporting
confidence: 78%
“…induces the trans-differentiation of VSMCs and stimulates the expression of AC8 (15). As an initial approach to determine whether there is any correlation between AC8 and Notch expressions in VSMCs, we analyzed their transcript expressions when treated with various concentrations of IL1␤.…”
Section: Notch 3 Expression Opposes Ac8 Expression-il1␤mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we observed that the regulatory effect of Tollip on VSMC proliferation and differentiation was independent of its secretion, since addition of Tollip antibody did not affect the effect of PDGF‐BB on VSMC (Figure S3). In addition to proliferation and phenotypic switching, the migrating VSMCs participate in the pathogenesis of neointima formation 19. To elucidate the role of Tollip in the migratory property of VSMCs, primary VSMCs derived from Tollip‐KO and Tollip‐TG mice were seeded into a Boyden chamber supplemented with or without PDGF‐BB (20 ng/mL) for 6 hours.…”
Section: Resultsmentioning
confidence: 99%